Toward precision smoking cessation treatment II: Proximal effects of smoking cessation intervention components on putative mechanisms of action. (1st February 2017) - Piper, Megan E.; Cook, Jessica W.; Schlam, Tanya R.; Smith, Stevens S.; Bolt, Daniel M.; Collins, Linda M.; Mermelstein, Robin; Fiore, Michael C.; Baker, Timothy B.
Highlights: Factorial experiments allow researchers to examine how person-factors influence response to individual intervention components. Self-reported psychiatric history affected response to smoking cessation counseling and combination nicotine replacement therapy duration. Participants who smoked more than a pack of cigarettes per day had a poorer response to smoking cessation counseling interventions. Abstract: Background: Understanding how smoking cessation treatments exert their effects can inform treatment development and use. Factorial designs allow researchers to examine whether multiple intervention components affect hypothesized change mechanisms, and whether the affected mechanisms are related to cessation. Methods: This is a secondary data analysis of smokers recruited during primary care visits (N = 637, 55% women, 87% white) who were motivated to quit. Participants in this fractional factorial experiment were randomized to one level of each of six intervention factors: Prequit Nicotine Patch vs None, Prequit Nicotine Gum vs None, Preparation Counseling vs None, Intensive In-Person Counseling vs Minimal, Intensive Phone Counseling vs Minimal, and 16 vs 8 Weeks of Combination Nicotine Replacement (nicotine patch + nicotine gum). Data on putative mechanisms (e.g., medication use, withdrawal, self-efficacy) and smoking status were gathered using daily assessments and during follow-up assessment calls. Results: Some intervention components influenced hypothesized mechanisms. Prequit Gum and Patch each reduced prequit smoking and enhanced prequit coping and self-efficacy. In-Person Counseling increased prequit motivation to quit, postquit self-efficacy, and postquit perceived intratreatment support. Withdrawal reduction and reduced prequit smoking produced the strongest effects on cessation. The significant effect of combining Prequit Gum and In-Person Counseling on 26-week abstinence was mediated by increased prequit self-efficacy. Conclusions: This factorial experiment identified which putative treatment mechanisms were influenced by discrete intervention components and which mechanisms influenced cessation. Such information supports the combined use of prequit nicotine gum and intensive in-person counseling as cessation interventions that operate via increased prequit self-efficacy.